2008
DOI: 10.1183/09031936.00018508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fudosteine on mucin production

Abstract: Fudosteine is a novel mucoactive agent, although little is known about how fudosteine decreases mucin production. The present study examined the effects of fudosteine on MUC5AC mucin synthesis and cellular signalling.An animal model of lipopolysaccharide (LPS)-induced inflammation and a bronchial epithelial cell line model of tumour necrosis factor (TNF)-a-induced inflammation were used. Fudosteine was administered before stimulation with LPS or TNF-a. The MUC5AC mucin levels were assayed and the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…At this dose, erdosteine was effective in reducing blood ROS levels in patients with COPD 65. Finally, fudosteine shows better bioavailability than NAC and reduces mucus secretion by inhibiting MUC5AC gene expression 66. Other potential therapeutic agents that are under development include Nrf2 activators, spin traps, redox sensor inhibitors, polyphenols, and enzyme mimetics, the details of which are beyond the scope of the current review 67,68…”
Section: Efficacy Of Antioxidant Supplementation In Preventing Progrementioning
confidence: 99%
“…At this dose, erdosteine was effective in reducing blood ROS levels in patients with COPD 65. Finally, fudosteine shows better bioavailability than NAC and reduces mucus secretion by inhibiting MUC5AC gene expression 66. Other potential therapeutic agents that are under development include Nrf2 activators, spin traps, redox sensor inhibitors, polyphenols, and enzyme mimetics, the details of which are beyond the scope of the current review 67,68…”
Section: Efficacy Of Antioxidant Supplementation In Preventing Progrementioning
confidence: 99%
“…Fudosteine decreased the number of goblet cells increased by lipopolysaccharide or b-stimulant in airway epithelium, and increased serous secretion in broncho-alveolar lavage fluid (BALF) of rats. It also has already reported that fudosteine inhibits MUC5AC mucin hypersecretion by reducing MUC5AC gene expression and the effects of fudosteine are associated with the inhibition of extracellular signal-related kinase and p38 mitogenactivated protein kinase in vivo and extracellular signalrelated kinase in vitro [1,2].…”
Section: Introductionmentioning
confidence: 94%
“…Fudosteine, [(−)-(R)-2-amino-3-(3-hydroxypropylthio)] propionic acid (Fig 2), has been used in the treatment of chronic respiratory diseases, such as bronchial asthma, chronic bronchitis, pulmonary emphysema, COPD, and bronchiectasis as a mucoactive agent [156157]. Fudosteine acts by increasing cysteine levels of the cells and has greater bioavailability than NAC.…”
Section: Small Molecule Thiol Antioxidantsmentioning
confidence: 99%
“…Fudosteine acts by increasing cysteine levels of the cells and has greater bioavailability than NAC. Fudosteine downregulates MUC5AC gene expression thus inhibits mucin hypersecretion [156]. Although, little is known about its mode of action, fudosteine has shown some promising potential in treatment of patients with COPD [158].…”
Section: Small Molecule Thiol Antioxidantsmentioning
confidence: 99%